Corporate Image Influencing Customers’ Purchase Decision In Minimarket In Bekasi - Rahmiati, Filda; Tahir, Md.Nor Hayati; Mubarak, Zulfikar (American Scientific Publishers, 2017)
This research is aimed to analyze Corporate Image toward Customers Purchase Decision that is measured through Quality, Performance, Responsibility, and Attractiveness with Purchase Decision. Corporate Image can be referred to the result for achieving a business growth. The methodology used in this research is quantitative approach by using primary data and questionnaire as the research instrument. The sampling technique used is non-probability technique with accidental sampling method and the sample size are 280 respondents who ever purchased products from Alfamart in Bekasi, Indonesia. Descriptive analysis and multiple regression analysis are adopted as tools for analyzing the result with significance level of 0.05. The result of research shows that Corporate Image has partially and simultaneously relationship with Purchase Decision and the contribution of Corporate Image toward Customer Purchase Decision is shown by coefficient of determination value (R 2) in which Corporate Image has influence of 45.2% on Purchase Decision, the rest of 54.8% is influenced by other factors that are not included in this research. Thus, Corporate Image has significant contribution to influence the Purchase Decision of customers in the market. It is advisable that the most purchased product need to create the private labels which can improve profit margins for the Alfamart itself.